Using Entrepreneurial Self-Efficacy as an Indirect Measure of Entrepreneurial Education - Najib A. Mozahem (14150970) (2021)
Business schools are under increasing pressure to demonstrate their educational achievements. In particular, some have questioned the utility of entrepreneurship education. As a result, measuring the knowledge and skills obtained from entrepreneurship education is crucial for both entrepreneurship programs as well as for business schools. While other studies have tried to measure entrepreneurship intent, this study seeks to validate and use a tool developed by Gedeon and Valliere (2018) in order to compare students who have taken an entrepreneurship course with students who have yet to take the course. Unlike the entrepreneurial intent measure, entrepreneurial self-efficacy, as developed by Gedeon and Valliere (2018), is founded on an educational assessment perspective, thereby seeking to augment a university degree program's learning outcomes. The measure is validated and tested using a sample of 560 students from four private universities in Lebanon. The results obtained using confirmatory factor analysis both support the internal consistency of the measure as well as support its utility as a tool to measure differences between both groups of students. The results show that in the sample used, the entrepreneurship course has led to an increase in entrepreneurial self-efficacy. Other Information Published in: The International Journal of Management Education License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ijme.2020.100385